Impact of Training by Family Doctor on Cadre Performance in Counseling at Posbindu Dusun Tahunan of Gunungkidul Regency - T. Herjuna Hadiyanta; Wahyudi Istiono; I Dewa Putu Pramantara (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2018)
Background: Increasing cases of non-communicable diseases (NCDs) are becoming a serious public health threat because they dominate the top 10 global causes of death. The government is trying to control it by way of early detection of NCDs risk factors through Posbindu (Integrated Coaching Groups) activities. At this time Posbindu programs are not running optimally because the volunteers called cadres (Kader) are not confident in doing counseling. Cadres find it difficult to read and understand the modules by themselves, while special training on counseling has not been prioritized. Optimally, family doctors as community oriented care providers need to train cadres to be skilled in counseling so that risk factors can be controlled as early as possible.Objectives: The purpose of this study was to assess whether the impact of role playing training by family physicians can improve the volunteer cadres’ performance in providing counseling compared with those who rely on only reading the modules.Methods: The design of this study was a quasi-experimental research with a sample size of 50 participants. The treatment was provided in the form of counseling to 11 volunteers (cadres) who were specially trained. Analysis of pre and post-test data used a variety of tests (t-test).Results: Cadres who were trained by family physicians showed a significant increase in mean knowledge level (p value 0.007) of 22.9. An average increase 4 weeks after training showed no significant difference (p value 0.346) when compared to results immediately after the training. Knowledge of cadres only reading the module showed no significant mean difference (p value 0.6871). There was a significant difference of mean knowledge between the trained cadres which was higher than the cadres who only read the modules (p value 0.005). There was also a significant increase in the average knowledge of participants after receiving counseling by trained cadres (p value 0.001) of 22.28.Conclusion: There was a significant increase in cadre knowledge about NCDs risk factors after being specially trained by family physicians. Knowledge of cadres before and after being given modules without training showed no significant change. There was also a significant increase in participants’ knowledge after receiving counseling by trained cadres. Training of cadres with role playing methods was demonstrated to increase participants’ knowledge significantly and can be considered a determinant of success in improving cadre performance in counseling.